PEMBENTUKAN UKS DI SDN 15 KUTA MAKMUR - Inong Sri Rahayu; Meutia Zuhra (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
School Health Unit is a means to improve the ability to live healthy and the health status of students as early as possible in order to improve student achievement. The program was carried out to improve student health through health education programs, health services and fostering a healthy school environment as an activity in the School Health Unit (UKS) aimed at the school community. Meanwhile, in Blang Adoe Village, Kuta Makmur District, North Aceh Regency, there was SD Negeri 15 Kuta Makmur, which did not yet have UKS. For this reason, the community service team wanted to do community service by establishing UKS at SD Negeri 15 Kuta Makmur. The establishment of UKS was a health activity carried out in schools with students and their environment as the main target. UKS establishment can be continued to the stage of UKS development to improve the ability to live and eat healthily, the dangers of juvenile delinquency, reproductive health education and formation of healthy living behavior, which will result in optimal health status. The implementation of UKS involved elements of health workers, school officers, students, local government, parents of students and other groups in the community